TYPES OF INTELLIGANCE TESTS THAT CAN BE USED IN PRIMARY AND SECONDARY SCHOOL CHILDREN - Irawan, Rizky Al Akbar (Jurnal Kopendik, 2025)
This study aims to identify various types of intelligence tests that are appropriate and suitablefor use with students at the elementary and secondary school levels. The method used in thisresearch is a literature study that focuses on a literature review. Based on the reviewed research,there are various types of intelligence tests that can be used to assess the cognitive abilities ofelementary and secondary school children. For elementary school children, some commonlyused tests include the Stanford-Binet, Wechsler Intelligence Scale for Children (WISC), ColouredProgressive Matrices (CPM), and Culture Fair Intelligence Test (CFIT). These tests help identifystudents' intellectual potential and special needs, both in learning aspects and overall academicdevelopment. Meanwhile, for secondary school students, tests such as the Wechsler AdultIntelligence Scale (WAIS), Multidimensional Aptitude Battery-II (MAB-II), and Intelligenz StructureTest (IST) are more commonly used. These tests help measure more complex intelligence andidentify an academic or career path that aligns with students' interests and talents, assistingthem in future planning.